‘The dream to know everything about everyone’: Affordances of commercial data systems and digital net-widening in policing - Hadjimatheou, Katerina (Theoretical criminology, 2025)
This article empirically analyses the use of new commercial integrated data systems in policing. We examine the impact of one of the most widely used commercial systems in the United Kingdon, through observations of platform use and in-depth interviews with users across ranks and strategic, tactical and operational roles; and across specialist units including criminal intelligence, ‘county lines’ organised crime and victim safeguarding. Drawing on analytical tools science and technology studies, our analysis nuances Cohen's seminal concept of net-widening by examining how digital policing is predicated on complex police–commercial relationships. We show how the data system itself generates affordances that drive insatiable data collection, transforms mundane encounters into surveillance opportunities, revalorises mundane information as intelligence, reconfigures the meaning of suspicion and disrupts the temporalities of policing itself. These undermine increasingly fragile principles of police legitimacy and due process, and raise concerns around transparency and accountability in policing.